Combining Traditional Ayurveda and Modern Technology: A Study on the Impact of Electric Fumigation with Natural Substances on Microbial Load (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Airborne diseases and nosocomial infections contribute significantly to recurring illness, financial burden, morbidity, and mortality. Traditional fumigation using natural substances has been extensively employed to combat various pathogens, yet scientific validation of its efficacy remains limited. This study aims to evaluate the effectiveness of herbal fumigation in reducing microbial load. We conducted controlled experiments in specific areas, measuring the microbial load of bacteria and fungi before and after fumigation using an electric fumigation device with selected herbs. Results indicated that electric fumigation significantly reduced microbial colonies, achieving a 40% reduction in bacterial colonies and a 32.75% reduction in fungal spores in location A, and even greater reductions of 62.5% and 91% in location B, respectively. The electric device ensured uniform fumigation without requiring an ignition agent, enhancing the process's convenience and safety. The findings suggest that combining plant-based fumigation with modern electric devices offers a safe, non-toxic, cost-effective, and efficient method for community-level sanitization. This study provides scientific validation for the ethnopharmacological use of herbal fumigation and supports its integration into public health strategies, particularly in settings where conventional methods are inaccessible or costly.